Evaluation of kinetic parameter and mechanical Properties of biobased Epoxy Adhesives in Wood-based Composites for Automotive Applications. (November 2021) - Aniol, A; Grosse, T; Fischer, F; Böhm, S
The relevance of sustainable structural materials is increasing in automotive components for sustainable construction. The sustainable material wood in particular can be used due to the very good specific mechanical material properties and has a high potential to be used as a structural material in hybrid constructions for the automotive components as an veneer laminate with modified epoxy adhesives. The material properties depend strongly on the interface between the capillary structure of the wood and the epoxy adhesive and also on the curing properties at the manufacturing process. In this study an epoxy adhesive (DGEBA) was copolymerized with lignosulphonate, a biobased waste product from the pulp and paper industry, as a sustainable coupling agent and the kinetic behavior of the macromolecular curing reactions and mechanical properties were characterized for wooden automotive components. The composites were characterized by differential scanning calorimetry (DSC) to investigate the curing kinetics of the biomodified adhesive. Subsequent a laminated veneer lumber was manufactured with beech veneer of 1 mm thickness. The mechanical properties of the composite structure were characterized by tensile tests, bending tests and tensile shear tests. The results show a significant improvement of the manufacturing time due to the kinetic behavior and the mechanical properties for structural components in the automotive industry.